Role of tuberculin skin test (Mantoux test) as an aid in the diagnosis of tuberculosis disease and to identify persons with latent tuberculosis in highly endemic hilly region of Jammu and Kashmir - Nazia Tabassum Sheikh; Sameera Akhtar; Shazia Tabassum; Sumat ul Khurshid (Eastern Journal of Medical Sciences, 2021)
Background: Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis and one of the major diseases affecting children throughout the world. Mantoux test and direct microscopic examination of acid-fast bacilli (AFB) by Ziehl–Neelsen staining are diagnostic and are widely being used. Objective: The objective of the study was to evaluate the efficacy of the Mantoux test and sputum smear examination as a diagnostic aid in latent TB. Materials and Methods: A prospective observational study was conducted, among 100 suspected cases of TB, over a period of 14 months from May 2019 to June 2020. After obtaining informed consent, patients were subjected to all three diagnostic tests including the Mantoux test, sputum smear examination for AFB, and cartridge-based nucleic acid amplification test (CBNAAT). Results of Mantoux and sputum tests were compared with CBNAAT to assess the sensitivity and specificity of individual tests. Results: In our study, most of the patients (32%) belonged to the age group of 21–30 years. There was a slight female predominance in the study population (52% females and 48% males). Mantoux test was positive in 41 (41%) patients and negative in 59 (59%) patients. On sputum examination, 42 (42%) patients tested positive and 58 (58%) patients were negative. On CBNAAT, 74 (74%) samples were positive, 26 (26%) were found to be negative. The sensitivity and specificity of the Mantoux test were 49.35% and 86.95%, respectively, and 53.33% and 92%, respectively, for sputum smear examination. Conclusion: Mantoux test, sputum smear, and CBNAAT test when performed together act as an aid in diagnosing TB in patients with latent TB.